Mortality analysis of patients with acute coronary syndrome receiving comprehensive cardiac care (KOS-Zawal) during the COVID-19 pandemic period - Grzegorz Kubielas; Dorota Diakowska; Michał Czapla; Catherine Ross; Przemysław Mitkowski; Izabella Uchmanowicz (Archives of Medical Science)
Introduction Due to the SARS-CoV-2 pandemic, there have been fundamental changes to the delivery and operation of healthcare facilities across the world, significantly impacting how patients with a variety of diseases are treated. We aimed to assess the impact of the COVID-19 pandemic on patient management outcomes among patients with acute coronary syndromes (ACS) and explore the differences in patients who were treated within and outside the coordinated care programme for patients after ACS (KOS-Zawal).